1982
DOI: 10.1139/v82-200
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of the hydrogénation catalytic activity of dinuclear complexes of rhodium(I) with the formation of carbonyl-bridged complexes

Abstract: Methanolic solutions of the dinuclear cationic complexes of rhodium(I), [Rh2(μ-X)(CO)2(Ph2ECH2EPh2)2]+ (X = Cl, Br; E = P, As) and iridium(I), [Ir2Cl(CO)3(Ph2PCH2PPh2)2], are each active catalysts for the hydrogenation of alkynes to alkenes, and alkenes to alkanes. Neutral complexes with pseudohalide ligands have also been investigated but only the cyano-complex [Rh2(CN)2(CO)2(Ph2PCH2PPh2)2], and the arsine analog, are of significant catalytic activity. Only those complexes which reversibly form bridged comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1983
1983
2013
2013

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…According to this scheme, the main pathway for production of 9 and 10 would be a simple SN2 reaction for step 1 followed by transient production of the unstable hydroxycarbonyl anion 13 (Scheme IV).…”
Section: Co (C6h5)3pmentioning
confidence: 99%
See 2 more Smart Citations
“…According to this scheme, the main pathway for production of 9 and 10 would be a simple SN2 reaction for step 1 followed by transient production of the unstable hydroxycarbonyl anion 13 (Scheme IV).…”
Section: Co (C6h5)3pmentioning
confidence: 99%
“…A catalytic cycle is proposed for this liquid-liquid system, in which it is shown that the catalyst (Bu4N+Co(CO)4") stays in the organic phase, and the product (the phenylacetate anion) is expelled into the aqueous phase. It is also shown that the rate-limiting reaction is not the nucleophilic displacement (1) (reaction of benzyl bromide with the cobalt carbonyl anion) but the cleavage of the acylcobalt carbonyl 4 by the ion pair Bu4N+OH" at the liquid-liquid interface. The presence of byproducts such as toluene and diphenylethane is accounted for in terms of the decomposition of a transient hydroxycarbonyl species 13 through loss of carbon dioxide.…”
mentioning
confidence: 99%
See 1 more Smart Citation